2015
DOI: 10.1111/hsc.12305
|View full text |Cite
|
Sign up to set email alerts
|

Pakistani women's use of mental health services and the role of social networks: a systematic review of quantitative and qualitative research

Abstract: Pakistani women in the UK are an at‐risk group with high levels of mental health problems, but low levels of mental health service use. However, the rates of service use for Pakistani women are unclear, partly because research with South Asian women has been incorrectly generalised to Pakistani women. Further, this research has been largely undertaken within an individualistic paradigm, with little consideration of patients’ social networks, and how these may drive decisions to seek help. This systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Thus, results cannot be generalized across minority groups based on ethnicity or sexuality. There is some evidence from other countries that some groups within LGBT communities and ethnic minorities are more at risk from MH crises and in need of supportive networks due to increased health needs coupled with limited access to social resources . Despite this, the study also has strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, results cannot be generalized across minority groups based on ethnicity or sexuality. There is some evidence from other countries that some groups within LGBT communities and ethnic minorities are more at risk from MH crises and in need of supportive networks due to increased health needs coupled with limited access to social resources . Despite this, the study also has strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have identified cultural factors that may influence help-seeking for South Asian groups. These include stigma [ 21 ], collectivist values and pluralistic treatment options [ 22 ], as well as religious beliefs and somatisation [ 15 ]. Although these findings highlight the role of individual differences and cultural “explanatory models” in help-seeking, they neglect the roles of systemic sociopolitical factors in causing and contributing to distress and healthcare systems in perpetuating underutilisation through their ongoing failures to address institutional racism and ethnic inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research has suggested that those from middle class backgrounds are more likely to participate in healthcare decisions than their counterparts [ 39 ]. Additionally, those from different ethnicities may have raised different issues [ 40 ]. Focus groups involved both service user and carer participants and, whilst this did not appear to be the case, it should be acknowledged that this might have impacted on the level of disclosure from service users and/or carers.…”
Section: Discussionmentioning
confidence: 99%